On scientific and medical personnel training courses at Academician V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs - art Editorial (Вестник трансплантологии и искусственных органов)
On scientific and medical personnel training courses at Academician V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs